1987
DOI: 10.1021/bi00381a015
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of a very high density lipoprotein from the hemolymph of the honeybee Apis mellifera

Abstract: A larval-specific very high density lipoprotein (VHDL) has been isolated from the hemolymph of the honeybee Apis mellifera. VHDL was isolated by a combination of density gradient ultracentrifugation and gel filtration. The purified protein is a dimer of Mr 160,000 apoproteins as shown by chemical cross-linking with dimethyl suberimidate. N-Terminal sequence analysis indicates that the two polypeptide chains are identical. The holoprotein contains 10% lipid by weight and 2.6% covalently bound carbohydrate. A na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Also, we showed that vitellogenin is a preferred target of oxidative carbonylation in comparison with apolipoprotein 1 and hexamerin, which similar to vitellogenin are major hemolymph proteins in adult bees (56)(57)(58). Preferential carbonylation has been described for Cu,Zn-superoxide dismutase (59, 60), a key antioxidant enzyme with metal-binding characteristics that are comparable with properties of vitellogenin.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Also, we showed that vitellogenin is a preferred target of oxidative carbonylation in comparison with apolipoprotein 1 and hexamerin, which similar to vitellogenin are major hemolymph proteins in adult bees (56)(57)(58). Preferential carbonylation has been described for Cu,Zn-superoxide dismutase (59, 60), a key antioxidant enzyme with metal-binding characteristics that are comparable with properties of vitellogenin.…”
Section: Discussionmentioning
confidence: 76%
“…Carbonylation intensities were expressed on a relative scale after normalization to the overall mean carbonylation intensity. Integrated intensities of protein bands were expressed as relative quantities after normalization to the mean integrated intensity of apolipoprotein 1, which is present at close to constant levels in adult bees (58). Production of hROS by immunocytes was analyzed by one-way ANOVA, in which treatment levels were assigned the following categorical factors: 1, cells from noninjected bees; 2, cells from bees injected with vehicle; 3, cells from bees injected with paraquat; and 4, cells reacted with 30% H 2 O 2 .…”
Section: Analysis Of Oxidative Damage In Tissuesmentioning
confidence: 99%
“…S1E). The only other members of this family characterized to date are the 160 kDa Melanization Enabling Protein of the beetle Tenebrio molitor (160MEP, also known as Melanization-related protein), which is found in the hemolymph of both sexes and enhances melanization reactions (Lee et al, 2000), and the 160 kDa Very High Density 1 to five candidate genes, using molecularly defined Exel deletions (Parks et al, 2004), recombination relative to w + P element insertions in w; cv-d 1 Pr/P element females and transposase-mediated recombination at P element insertions (Chen et al, 1998) Lipoprotein (VHDL) found in the larval hemolymph of the honeybee Apis mellifera (Shipman et al, 1987). Unlike insect yolk Vtgs (Tufail and Takeda, 2008), members of the Cv-d/160MEP family are not cleaved into smaller fragments prior to secretion, either in vivo (Shipman et al, 1987;Lee et al, 2000) or in vitro (supplementary material Fig.…”
Section: Cv-d Is a Vitellogenin-like Proteinmentioning
confidence: 99%
“…It is annotated as 'hypothetical protein' with a predicted mass of 173kDa in the NCBI database. However, it has been isolated previously from larval haemolymph and assigned as 'very high density lipoprotein' (VHDL) by Shipman et al (Shipman et al, 1987). Determination of the N-terminal amino acid sequence of the secreted VHDL by Edman degradation carried out by this group (Shipman et al, 1987) revealed its relationship to HP 173.…”
Section: Development Of In Vitro Reared Drone Larvaementioning
confidence: 99%
“…However, it has been isolated previously from larval haemolymph and assigned as 'very high density lipoprotein' (VHDL) by Shipman et al (Shipman et al, 1987). Determination of the N-terminal amino acid sequence of the secreted VHDL by Edman degradation carried out by this group (Shipman et al, 1987) revealed its relationship to HP 173. Throughout the total larval development, imaginal disc growth factor 4 (IDGF 4) and ferritins 1 and 2 are available at rather constant levels.…”
Section: Development Of In Vitro Reared Drone Larvaementioning
confidence: 99%